Longitudinal serum chloride trajectories and their correlation with all-cause mortality in critically Ill sepsis patients: a retrospective cohort analysis - Min Lei; Mingyue Ma; Yaping Zhang; Nianqiang Hu; Junran Xie (BMC Infectious Diseases)
Abstract Background Sepsis, a critical organ failure caused by an abnormal host response to infection, continues to be a significant worldwide medical issue. Despite advances in early recognition and treatment, sepsis mortality remains high, particularly in severely ill individuals. Serum chloride, a key electrolyte in the balance of acids and bases and fluid homeostasis, has emerged as a potential prognostic marker in sepsis. However, previous studies have primarily relied on single time-point measurements, which fail to capture the dynamic changes in chloride levels during sepsis progression. Methods Using information from the Medical Information Mart for Intensive Care IV database, we incorporated 6,219 adult sepsis cases diagnosed according to the Sepsis-3 criteria. Group-based trajectory modeling was employed to determine distinct serum chloride trends through the first 5 days of ICU stay. Baseline parameters, laboratory measurements, and clinical scores were contrasted across trajectory groups. The principal outcome was all-cause mortality at 28- and 365 days. The association between serum chloride trajectories and mortality was evaluated utilizing Cox proportional hazards models, with adjustments made for possible confounding factors. Sensitivity and subgroup analyses were carried out to validate the results. Results Four distinct serum chloride trajectories were identified: Class 1 (n = 554, 8.9%), Class 2 (n = 3,288, 52.9%), Class 3 (n = 2,063, 33.2%), and Class 4 (n = 314, 5.0%). Patients in Class 4, characterized by elevated serum chloride levels, had the highest mortality. Compared to Class 1, Class 4 had significantly higher mortality in both 28 days (HR: 2.04, 95% CI 1.53–2.71) and 365 days (HR: 1.90, 95% CI 1.52–2.37) after adjusting for confounders. Sensitivity analyses excluding patients with malignancy and subgroup analyses categorized by age, gender, and comorbidities confirmed the robustness of these findings. Conclusion Longitudinal serum chloride trajectories strongly correlate with short-term and long-term mortality in sepsis patients. Elevated serum chloride levels (Class 4) are associated with the highest mortality risk, highlighting the importance of dynamic monitoring of serum chloride as an important prognostic instrument for risk classification and personalized treatment in sepsis management.